Design of Reactor for the Production of Zinc Ferrite - Fathiyah Afriani Anshari; Asep Bayu Dani Nandiyanto; Risti Ragaditha (Acta Chimica Asiana, 2022)
The development and analysis of a reactor design for the manufacture of zinc ferrite is the aim of this study. The design employs a Continuous Stirred Tank Reactor (CSTR) type, with the tank and stirrer serving as the reactor's primary structural elements. The requirements for the built tank and stirrer will significantly impact the safety and production of silicon dioxide. As a result, Microsoft Excel is used for the calculation process for designing this reactor. The results of the calculations are obtained for design pressure 4,304 psig, cylinder thickness 0.07 in, top cover thickness 0.07 in, top cover height 12.39 in, bottom cover thickness 0.08 in, bottom cover height 21.18 in, reactor height 44.34 in, impeller length 5.43 in, stirring power 5 hp and shaft length 15.98 in. This design can become a reference for the production of zinc ferrite to make it more efficient in the production process.